The Role of Monoaminergic Neurotransmission for Metabolic Control in the Fruit Fly Drosophila Melanogaster - Li, Yong; Tiedemann, Lasse; von Frieling, Jakob; Nolte, Stella; El-Kholy, Samar; Stephano, Flora; Gelhaus, Christoph; Bruchhaus, Iris; Fink, Christine; Roeder, Thomas (Frontiers in Systems Neuroscience, 2017)
Hormones control various metabolic traits comprising fat deposition or starvation resistance. Here we show that two invertebrate neurohormones, octopamine and tyramine as well as their associated receptors, have a major impact on these metabolic traits. Animals devoid of the monoamine octopamine develop a severe obesity phenotype. Using flies defective in the expression of receptors for octopamine and tyramine, we aimed to decipher the contributions of single receptors for these metabolic phenotypes. Whereas those animals impaired in octß1r, octß2r, and tar1 share the obesity phenotype of octopamine deficient (tβh-deficient) animals, the octß1r, octß2r deficient flies show reduced insulin release, which is opposed to the situation found in tβh deficient animals. On the other hand, OAMB deficient flies are leaner than controls, implying that the regulation of this phenotype is more complex than anticipated. Other phenotypes seen in tβh-deficient animals, such as the reduced ability to perform complex movements tasks can mainly be attributed to the octß2r. Tissue specific RNAi experiments revealed a very complex interorgan communication leading to the different metabolic phenotypes observed in octopamine or octopamine and tyramine deficient flies.